Form identification of purple flying squid (Sthenoteuthis oualaniensis) based on gladius morphology - Zhu, Kai; Lin, Dongming; Chen, Xinjun; Xu, Kaida (Frontiers in Marine Science, 2022)
Stock structure information is an important part of bases for understanding the dynamics of cephalopod populations. Purpleback flying squid Sthenoteuthis oualaniensis is an abundant and highly productive species in tropical and subtropical waters of the Indo-Pacific region. However, it is characterized by a complex stock structure and the stock discrimination is an urgent priority to understand basic biology and for stock assessment and management purposes. Here, we used gladius morphology to identify and discriminate the dwarf without a dorsal photophore and middle-sized typical forms of S. oualaniensis in the South China Sea. Result showed that both forms had double-axes on the gladiusand females consistently had larger gladius than males. Multivariate analyses using the gladius morphometric characteristics indicated that individuals of dwarf form without a dorsal photophore were distinguished from that of middle-sized typical form, which was evidenced by the obvious groups and significant dissimilarity of gladii of these two forms. The discrimination based on the gladius morphometric characteristics showed a high rate of accuracy, in which a global discrimination accuracy was estimated 92.36% for both forms without regarding sexes and 65.82% for the discrimination to form and sex. In combination, these lines of evidence indicated that individuals of dwarf without a dorsal photophore and middle-sized typical forms of S. oualaniensis can be accurately distinguished using the gladius morphometric characteristics and these results will warrant application of gladius to study the stock structure of S. oualaniensis and other squid else.